Serum IL-17F as a biomarker of infection-independent cirrhosis progression - Konstantis, Georgios; Passenberg, Moritz; Guntlisbergen, Clara; Schütte, Andreas; Jung, Björn; Nuruzade, Nargiz; Seltsam, Florian; Hoyer, Dieter P.; Best, Jan; Willuweit, Katharina; Schmidt, Hartmut H.; Guckenbiehl, Sabrina; et al. (Frontiers in Immunology, 2025)
BackgroundCirrhosis-associated immune dysfunction (CAID) is characterized by a dysregulated immune response involving both systemic inflammation and immunosuppression, frequently culminating in acute-on-chronic liver failure (ACLF). The IL-23/IL-17 signaling axis is a key inflammatory pathway implicated in various immune-mediated diseases, yet its specific role in cirrhosis remains poorly understood.MethodsIn this prospective observational study, we analyzed circulating levels of IL-23, IL-17A, IL-17E, IL-17F, IL-1β, and IL-1RA in 127 patients with compensated cirrhosis, acute decompensation (AD), or ACLF in the absence of active infection. Cytokines were quantified by ELISA and correlated with disease severity, organ dysfunction, and clinical outcomes. Multivariable ordinal and multinomial regression analyses were performed to assess associations between cytokines and cirrhosis progression.ResultsLevels of IL-17F, IL-23, and IL-1β levels were significantly lower in patients with AD and ACLF compared to those with compensated cirrhosis. In contrast, IL-17A, IL-17E, and IL-1RA levels remained largely unchanged. IL-17F was independently associated with reduced odds of progression to AD or ACLF, suggesting a possible protective role. IL-17F also retained an inverse association with disease severity in adjusted ordinal regression models.ConclusionIL-17F expression declines progressively with increasing severity of liver disease, independently of IL-17A. These findings support a distinct, possibly immunoregulatory role for IL-17F in cirrhosis progression, and warrant further mechanistic investigation into its functional relevance as a biomarker for disease stratification or as a therapeutic target.